2013
DOI: 10.1111/hdi.12061
|View full text |Cite
|
Sign up to set email alerts
|

Methicillin‐resistant Staphylococcus aureus carriage in hospitalized chronic hemodialysis patients and its predisposing factors

Abstract: There has been a paucity of literature on methicillin-resistant Staphylococcus aureus (MRSA) colonization in chronic hemodialysis patients who required admission. The purpose of this study is to determine the MRSA carriage rate in hospitalized chronic hemodialysis patients, to identify the risk factors, and assess the consequences of MRSA colonization. This was a retrospective study of hospitalized chronic hemodialysis patients at Khoo Teck Puat Hospital from July 1, 2010 to June 30, 2011. MRSA screening was d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 22 publications
(43 reference statements)
1
11
1
Order By: Relevance
“…28,30,33,42,43,46 Two of these studies reported the MRSA infection rate during hospitalization of inpatient individuals, 33,43 whereas four studies included data after a long-term follow-up period of outpatient individuals. 28,30,42,46 Because we were interested in the long-term risk of acquiring a MRSA infection, only the data from the latter four studies were used and the data from each study are summarized in Table 3.…”
Section: Resultsmentioning
confidence: 99%
“…28,30,33,42,43,46 Two of these studies reported the MRSA infection rate during hospitalization of inpatient individuals, 33,43 whereas four studies included data after a long-term follow-up period of outpatient individuals. 28,30,42,46 Because we were interested in the long-term risk of acquiring a MRSA infection, only the data from the latter four studies were used and the data from each study are summarized in Table 3.…”
Section: Resultsmentioning
confidence: 99%
“…10,12,13,15 Difference in length of time on haemodialysis among colonized and noncolonized dialysis patients was assessed through three studies, but no statistically significant trend was found (P ¼ 0.934). 10,12,16 Finally, the gender (RR: 0.97, male; 95% CI: 0.53e1.81; Q ¼ 9.06; P for heterogeneity ¼ 0.06) (Supplementary Figure S8) did not display significant association with colonization. 8,10,12,16 A smaller number of studies provided some additional findings.…”
Section: Resultsmentioning
confidence: 93%
“…10,12,16 Finally, the gender (RR: 0.97, male; 95% CI: 0.53e1.81; Q ¼ 9.06; P for heterogeneity ¼ 0.06) (Supplementary Figure S8) did not display significant association with colonization. 8,10,12,16 A smaller number of studies provided some additional findings. Two studies, with 300 patients total, provided data on history with MRSA colonization or infection and our analysis indicated that patients with previous history of colonization or infection were more likely to be colonized with this same pathogen (RR: 7.61; 95% CI: 3.43e14.98; Q ¼ 0.35; P for heterogeneity ¼ 0.554).…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations